1988
DOI: 10.1007/bf01013910
|View full text |Cite
|
Sign up to set email alerts
|

Sex pheromone components of the oblique-banded leafroller,Choristoneura rosaceana in the Okanagan Valley of British Columbia

Abstract: (Z)-11-Tetradecen-1-yl acetate, (E)-11-tetradecen-1-yl acetate, and (Z)-11-tetradecen-1-ol were previously reported as the sex pheromone in New York strains of the oblique-banded leafroller,Choristoneura rosaceana (Harris), and (E)-11-tetradecen-1-ol was tentatively identified in female tip extracts. For Okanagan Valley strains ofC. rosaceana, an additional component, (Z)-11-tetradecenal, was identified from female tip extracts by split-less capillary gas-liquid chromatography and mass spectroscopy and was str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 18 publications
0
56
0
Order By: Relevance
“…Despite the importance and specificity of the 3 minor pheromone components in the attractiveness of the sex pheromone blend for male C. rosaceana in western North America (Vakenti et al 1988, Thomson et al 1991, we failed in a series of both small-plot and field-cage studies to show any significant role of the minor components Zll-14:Ald and Zll-14:0H in disruption. Similarly, Agnello et al (1996) found no difference in the level of disruption by using dispensers loaded with either a 94:6 Z:Ell-14:0Ac blend or a 90:5:5 Z:Ell-14:0Ac: Zll-14:0H blend in New York.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Despite the importance and specificity of the 3 minor pheromone components in the attractiveness of the sex pheromone blend for male C. rosaceana in western North America (Vakenti et al 1988, Thomson et al 1991, we failed in a series of both small-plot and field-cage studies to show any significant role of the minor components Zll-14:Ald and Zll-14:0H in disruption. Similarly, Agnello et al (1996) found no difference in the level of disruption by using dispensers loaded with either a 94:6 Z:Ell-14:0Ac blend or a 90:5:5 Z:Ell-14:0Ac: Zll-14:0H blend in New York.…”
Section: Discussionmentioning
confidence: 93%
“…Hill and Roelofs (1979) and Vakenti et al (1988) found that Ell-14:0Ac comprised ~ 1-2% of female abdominal tip extracts. Maximal moth catches were with acetate blends, including 3-5% of this isomer with populations in N ew York (Hill and Roelofs 1979).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of C. rosaceana, the attracticide was loaded with a mixture containing 95.5% of cis-11-tetradeca-1-acetate (Z11-14Ac following the nomenclature used by Stevens, 1998), 2% of trans-11-tetradeca-1-acetate (E11-14Ac), 1.5% of cis-11-tetradeca-1-alcohol (Z11-14OH), and 1% of cis-11-tetradeca-1-aldehyde (Z11-14Al). This was based on the blend reported by Vakenti et al (1988). In the case of P. pyrusana, the proportions of pheromone components in the attracticide were 94% of cis-11-tetradeca-1-acetate (Z11-14Ac) and 6% of cis-9-tetradeca-1-acetate (Z9-14Ac).…”
Section: Methodsmentioning
confidence: 99%
“…Greater success has been recorded with a Western population of obliquebanded leafroller in British Columbia, Canada (Evenden et al, 1999a,b). The females of this Western population contain different amounts and ratios of the four-component pheromone and the males are characterized by different behavioral and antennal responsiveness to blends of these four components as compared with Eastern U.S. populations of this species (Vakenti et al, 1988, Thomson et al, 1991El-Sayed et al, 2003). Despite numerous studies on mating disruption of these two species, the mechanisms behind its effectiveness are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%